PIRAMIDA DEIKSIS PEREMPUAN MINANGKABAU - Sheiful Yazan (Kafa`ah: Journal of Gender Studies, 2011)
Over eighty deixis for Minangkabau women. These words is spread on a shole variety of Minangkabau speech acts. Study of Critical Discourse Analysis Pragmatics about deixis will give an overview of the “inner phylosophy” of a society. This paper are expected to be obtained an idea of how society treats Minangkabau women through speech acts. There are 75 out of 81 womwn roles/positions of honor, intimate, and egalitarian; There are only two negative positions. Conclusion: Minangkabau society treats women honorably in the 93% speech acts; only 2,4 % f speech acts form of contempt/social punishment.Keywords : Deixis, Minangkabau, Pragmatics, Critikal Discourse Analysis, Inner phylosophy, speech acts, deixis clasificationCopyright © 2011 by Kafa`ah All right reservedDOI : 10.15548/jk.v1i2.74